(untitled) (World Bulletin of Social Sciences, 2023)
This article analyzes the question of qualification in international civil proceedings, and examines their differences in national procedural law and international private law. In the article, a number of foreign scientists, including Clarkson and Hill, I.V. Getman-Pavlova, V.P. The views of Zvekov, Biryukova.N.S., Kuznetsov M.N. and other scientists were studied. Also, Chisinau Convention "On Legal Assistance and Legal Relations in Civil, Family and Criminal Matters", Hague Convention "On Civil Procedure Matters", Civil Procedure Code of the Republic of Uzbekistan and The Economic Procedural Code of the Republic of Uzbekistan was analyzed. Important theoretical conclusions were made on the issues analyzed in the article and a number of proposals were presented